BCG Vaccination at Birth and Rate of Hospitalization for Infection Until 15 Months of Age in Danish Children: A Randomized Clinical Multicenter Trial. (7th April 2018) - Stensballe, Lone Graff; Ravn, Henrik; Birk, Nina Marie; Kjærgaard, Jesper; Nissen, Thomas Nørrelykke; Pihl, Gitte Thybo; Thøstesen, Lisbeth Marianne; Greisen, Gorm; Jeppesen, Dorthe Lisbeth; Kofoed, Poul-Erik; Pryds, Ole; Sørup, Signe; et al.
Abstract: Background: The bacillus Calmette-Guérin (BCG) vaccine against tuberculosis might reduce the non–tuberculosis-related child mortality rate in low-income settings. We tested the hypothesis that BCG vaccination at birth would reduce early childhood hospitalization for infection in Denmark, a high-income setting. Hospitalization for infection was a secondary outcome in a randomized trial with the primary aim to estimate the potential non-specific effects of BCG vaccination at birth on all-cause hospitalization. Methods: A total of 4262 children included in the Danish Calmette Study were assigned randomly to either receive the BCG vaccine or not and were followed through the Danish National Patient Register. The outcome was number of hospitalizations for infection until the age of 15 months. Data were analyzed by Cox regression in intention-to-treat (ITT) and per-protocol (PP) analyses. Results: In the ITT analysis, we observed 588 hospitalizations for infection (mean, 0.28 hospitalization per child) among the 2129 children allocated to receive the BCG vaccine and 595 hospitalizations for infection (mean, 0.28 hospitalization per child) among the 2133 children allocated to the control group (hazard ratio [HR], 0.99 [95% confidence interval (CI), 0.85–1.15]). The PP analysis yielded an HR of 1.00 (95% CI, 0.86–1.16). Predefined interaction ITT analyses showed that among 740 children with a BCG-vaccinated mother, the HR for BCG-vaccinated children was 0.65 (95% CI, 0.45–0.94); the HR for children who had a non–BCG-vaccinated mother was 1.10 (95% CI, 0.93–1.29) ( P = .01, test of no interaction). Cesarean delivery modified the effect of BCG vaccination (HRs, 0.73 [95% CI, 0.54–0.99] in children born by cesarean section vs 1.10 [95% CI, 0.92–1.30] in other children; P = .02). When the outcome was defined as time to first hospitalization, the HR for premature children after BCG vaccination was 1.81 (95% CI, 0.95–3.43), whereas the HR was 0.94 (95% CI, 0.82–1.08) for children born at term ( P = .05). Conclusion: BCG vaccination did not affect the rate of hospitalization for infection up to the age of 15 months in Danish children. In future studies, the role of maternal BCG-vaccination, premature birth, and cesarean delivery needs further exploration. Abstract : In this large-scale randomized controlled trial that included 4262 Danish infants, vaccination against BCG did not affect the rate of hospitalization for infection up to the age of 15 months. In future studies, the role of maternal vaccination against BCG, premature birth, and cesarean delivery in BCG-vaccinated children needs further exploration.